Study of molten aluminium cleaning process using physical modelling and CFD - Song, Jin L.; Chiti, Fabio; Bujalski, Waldemar; Nienow, Alvin W.; Jolly, Mark R. (TMS (The Minerals, Metals & Materials Society), 2004)
Furnace treatment is an important step during molten aluminium production by which the dissolved hydrogen and solid impurity particles are removed. Conventionally, a chlorine/inert gas mixture is used for this purpose injected into the molten metal via a simple lance. In order to meet new requirements for furnace emissions and improve efficiency, mechanical agitation through an impeller is becoming more widely used. In this research, the homogenization behaviour of both lance bubbling and mechanical agitation by impeller has been investigated experimentally and numerically. It can be concluded that under the same mean specific energy dissipation rates, the velocity magnitude for mechanical agitation process is about ten times bigger than that for the lance bubbling process, and the mixing time for the mechanical agitation process are much lower than that for the lance bubbling process, so better cleaning or fluxing would be expected.
Keywords: molten aluminum; CFD; impeller; PIV; mixing